Qualification of green areas in the city of São Carlos (São Paulo state): analysis of uses and environmental management proposals focusing on the small watershed stream of Santa Maria do Leme - Peres, Renata Bovo; Figueiredo, Andréia Nasser; Iared, Valéria Ghisloti; Munhoz, Pedro Augusto; Oliveira, Haydée Torres de (Sociedade & Natureza, 2018)
This study aimed to generate subsidies for the qualification of green areas system in the city of São Carlos (São Paulo State) based on the analyses of use, suitability and educational potentialities of the green areas of small watershed of Santa Maria do Leme stream. The investigation was divided into two phases: the first one was concentrated on general analysis of 33 leisure public areas and 22 institutional public areas of the small watershed, considering as main category, the adequacy of use. The second phase considered the selection of five public areas of the small watershed, aiming to develop a qualitative assessment of these spaces according to legislation and management aspects, accessibility, landscape features, flora, fauna, perceptual attributes and socio-cultural practices. The results demonstrated that most of these spaces are inappropriate in terms of uses and social environmental functions, because they are badly located and unattractive for collective uses. The presence of the water body as a structuring element of a system of green areas is a potentiality in terms of connectivity. The analyses pointed out the problematic relationship between environmental management and educational aspects in urban green areas, important factor for the formulation of public policies to promote more socially and environmentally integrated cities.